2015
DOI: 10.3141/2520-11
|View full text |Cite
|
Sign up to set email alerts
|

Level-of-Service Model for Protected Bike Lanes

Abstract: Several methods exist for quantifying the quality of service provided by a roadway from a bicyclist's perspective; however, many of these models do not consider physically protected bike lanes and, of those that do, none is based on empirical data from the US. This is problematic as engineers, planners, and elected officials are increasingly looking to objective performance measures to help guide transportation project design and funding prioritization decisions. This paper addresses this gap by presenting a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…This separation can also make drivers more comfortable in the presence of cyclists [90]; however, on-road lanes are often a more practical and less costly alternative for cities and planning authorities [75]. Many indices have been developed for both on-street and off-street facilities, yet many of them do not consider physically protected bike lanes [91,92]. Li et al [93] investigated cyclists' perceptions of comfort in physically separated facilities in China.…”
Section: Sharing Policymentioning
confidence: 99%
See 1 more Smart Citation
“…This separation can also make drivers more comfortable in the presence of cyclists [90]; however, on-road lanes are often a more practical and less costly alternative for cities and planning authorities [75]. Many indices have been developed for both on-street and off-street facilities, yet many of them do not consider physically protected bike lanes [91,92]. Li et al [93] investigated cyclists' perceptions of comfort in physically separated facilities in China.…”
Section: Sharing Policymentioning
confidence: 99%
“…These factors included the type and volume of agents, the proportions of e-bikes and e-scooters, the peak periods, the physical separations between the motorized and bicycle and pedestrian lanes, bicycle lane slopes, roadside access points and land usage. Foster et al [91] conducted a BLOS study for protected bicycle lanes in the US. They concluded that the type of buffer, the direction of travel, the adjacent motor vehicle speed limit and the average daily motor vehicle volumes significantly affected cyclists' comfort when using these facilities.…”
Section: Sharing Policymentioning
confidence: 99%
“…This approach could have been done using an online survey, though is very difficult in person or with a group due to the need to adapt the pairs based on selections. Other studies, particularly those examining bicycle level-of-service have presented images or video clips in person to groups of respondents (e.g., Foster et al, 2015 andPetritsch et al, 2010). This approach better enables the researchers to control factors such as screen/image size, audio quality and volume, among other factors.…”
Section: Survey Designmentioning
confidence: 99%
“…Supplementary methods to the initial list were found through snowballing of references and searches in the Scopus database. The criterion results in the exclusion of such methods as those that are focused solely on intersections [18], separated bicycle or shared paths [19][20][21], rural areas [22,23], urban arterials [24], or bicycle lanes [25,26]. Audit-based metrics are also excluded from Table 1, including those in Australia and the UK that use the term "Cycling Level of Service" [9,27,28] and select others that use the term bicycle level of service but are either 'scorecard' based or lack an empirical foundation for the combination of variables [29,30].…”
Section: Introductionmentioning
confidence: 99%